Inflation expectations and inflation uncertainty in the Eurozone : evidence from survey data - Ivo J. M. Arnold; Jan J. G. Lemmen (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper uses the European Commission's Consumer Survey to assess whether inflation expectations have converged and whether inflation uncertainty has diminished following the introduction of the Euro in Europe. Consumers? responses to the survey suggest that inflation expectations depend more on past national inflation rates than on the ECB's anchor for price stability. The convergence in inflation expectations does not appear to be faster than the convergence in actual inflation rates. Regarding inflation uncertainty, the data indicate a relationship with country size, suggesting that within EMU, inflation uncertainty may increase in countries that have a smaller influence on ECB policy.
Keywords: D84; E31; E58; 330; monetary union; inflation differentials; consumer survey; Inflationserwartung; Inflationsrate; Inflationskonvergenz; Risiko; Schätzung; Europäische Wirtschafts- und Währungsunion; EU-Staaten